Sargassum: the atypical irruption of an ancient ecosystem - Gustavo Martínez-González (Instituto Nacional de Salud Pública, 2019)
Sargassum constitutes an ancient marine ecosystem that circulates clockwise on the Atlantic Ocean. Upon 2011, the pelagic seaweed which is the main component of sargassum started to reach beaches on 19 Caribbean countries, with environmental, health and economic impacts that need to be addressed urgently.